Long-Term Safety and Efficacy of Percutaneous Left Atrial Appendage Closure with the LAmbre Device - Guangji Wang; Bin Kong; Yu Liu; He Huang (Journal of Interventional Cardiology)
Background. Left atrial appendage closure (LAAC) using the LAmbre device has been associated with prevention of stroke in patients with nonvalvular atrial fibrillation (AF). Here, we interrogated the long-term safety and efficacy of using the LAmbre device in percutaneous LAAC. Methods. We analyzed 56 records of patients with nonvalvular AF undergoing LAAC procedures with the LAmbre device. We collected and analyzed the data to define the safety and efficacy of the LAmbre device implantation. Result. The LAAC was successfully occluded in the 56 patients. Our data showed no serious residual leak or pericardial effusion occurred during the perioperative period. At a mean follow-up of 37.8 ± 23.5 months, there were 7.1%, 3.6%, and 3.6% rates of death, stroke, and device-related thrombus, respectively. There were no cases of severe residual leak or systemic embolism. Conclusion. Taken together, we demonstrate that execution of LAAC with the LAmbre device has high procedural success and prevents AF-related stroke. However, further large-scale trials might be required to confirm our findings.